VACHA (ACORUS CALAMUS LINN.): A VALUABLE MEDICINAL PLANT - Gagan deep, Kour; AK, Sharma; Sanghamitra, Dash; Nigamanand, Bal (International Journal of Ayurveda and Pharma Research, 2015)
Last few decades have again shown a notable resurgence of interest in medicinal plants. The reason behind is the increasing awareness about the limitations of the synthetic chemotherapeutic agents. Now herbal medicines and natural products are in big demand all over the world. One of the important medicinal plant used in Ayurveda traditional medicine to treat different ailments and maintain health condition is Vacha (Acorus calamus Linn.). It is a herbaceous perennial belonging to family Araceae. Vacha is one of the most renowned herbs of the ancient Vedic seer as a rejuvenative for the brain and nervous system. Vacha stimulates the power of self expression and intelligence. Rhizome of Acorus calamus Linn. Contain calamediol, essential oil, tanning substances and vitamin C. These constituents are valuable in a vast range of diseases. Vacha has a special potency as a nervine tonic. It is a very vigorous brain tonic, because it shows results in a very short time. It increases the overall memory of the person and strengthens the nervous system. Vacha is prescribed to people who have amnesia. Improving the memory is a quest on which human beings have embarked centuries ago. In almost all civilizations, there have been attempts to discover the best herbs for brain enhancement with minimum side effects. Perhaps, Ayurveda wins the race in this. All the herbs Ayurveda uses for its brain tonics have minimum side effects and are quite safe for the human beings. Western science is now warming up to these herbs and is looking upon them as effective supplements for the human brain. It works well in digestive ailments like flatulence, loss of appetite, distaste, abdominal dull pain and worms. Vacha relieves the phlegm, eases cough and asthma. It is also useful to reduce fever. It is also highly useful for the treatment of epilepsy and other mental ailments.